Growing into Relative Income Poverty: Urban China 1988 to 2013 - Björn Anders Gustafsson; Ding Sai (Institute of Labor Economics (IZA), 2019)
This paper presents several arguments for applying a relative poverty line to urban China. For example between 2002 and 2013 urban residents in China changed their assessment of how much money that is necessary. Data from the China Household Income Project indicate that while, assessed against an absolute poverty line, poverty among Chinese urban residents was already fairly low in 2007, increasing proportions fell under a relative poverty line from 1988 to 2007. Thus income growth in urban China was more rapid in the middle segments of the income distribution that at it's lower segments. In 2013, at least as large fractions of the urban population as in many rich countries were deemed poor in relative terms. We also specify and estimate logit models for 2002 and 2013 after first having divided the samples into children, adults and elderly people. We find that the risk of being relative poor in urban China both years under study was positively associated with lack of work among adult household members, a low education of the household head, living in a low-income city, the number of children, and being aged and not receiving a pension. Pensions for the aged in combination with co-residency with adult children or with other adults have kept poverty rates among the increasing number of elderly in urban China from exceeding those among adults. In contrast, relative poverty rates are somewhat higher among children than among the entire urban population.
Keywords: I3; I32; 330; urban China; poverty; subjective poverty line; children; adults; older people